2017
DOI: 10.1016/j.prro.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Palliative radiation therapy for bone metastases: Update of an ASTRO Evidence-Based Guideline

Abstract: Updated data analysis confirms that radiation therapy provides excellent palliation for painful bone metastases and that retreatment is safe and effective. Although adherence to evidence-based medicine is critical, thorough expert radiation oncology physician judgment and discretion regarding number of fractions and advanced techniques are also essential to optimize outcomes when considering the patient's overall health, life expectancy, comorbidities, tumor biology, anatomy, previous treatment including prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
295
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(315 citation statements)
references
References 35 publications
5
295
0
15
Order By: Relevance
“…The radiation protocols used here were prescribed based on the best judgment of radiation oncologists considering patient characteristics, including tumor size, and normal tissue response. Interestingly, multiple meta‐analyses of dose‐fractionation trials in people receiving palliative radiotherapy for various tumors, including bone metastasis, lung cancer, and rectal cancer, found that various palliative protocols confer comparable results . There is no evidence that any regimen provides greater or more durable palliation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiation protocols used here were prescribed based on the best judgment of radiation oncologists considering patient characteristics, including tumor size, and normal tissue response. Interestingly, multiple meta‐analyses of dose‐fractionation trials in people receiving palliative radiotherapy for various tumors, including bone metastasis, lung cancer, and rectal cancer, found that various palliative protocols confer comparable results . There is no evidence that any regimen provides greater or more durable palliation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, multiple meta-analyses of dose-fractionation trials in people receiving palliative radiotherapy for various tumors, including bone metastasis, lung cancer, and rectal cancer, found that various palliative protocols confer comparable results. [22][23][24][25][26] There is no evidence that any regimen provides greater or more durable palliation.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that single fraction radiotherapy was as effective as multifraction regimens in palliation of bone metastases but retreatment was more frequent in the single fraction regimen [15-20]. A recent update of the ASTRO (American Society of Therapeutic Radiology and Oncology) evidence-based guideline regarding palliative radiotherapy for painful bone metastases concluded that there was strong evidence of pain relief equivalency between single and multiple fraction regimens for bone metastases [21]. Similar results were observed in our present study wherein there was no statistical difference in complete pain relief (20% in each group) and overall pain relief (80%, 75% and 85% in groups I, II and III, respectively (P = 0.7).…”
Section: Discussionmentioning
confidence: 99%
“…Palliative radiotherapy (RT) is widely used to alleviate symptoms, especially in patients with painful bone metastasis, and high response rates of 70%‐80% have been reported in these patients . Palliative RT is considered a safe treatment, and severe adverse events associated with palliative RT alone are rare .…”
Section: Introductionmentioning
confidence: 99%